2022
DOI: 10.1108/ijoem-08-2021-1215
|View full text |Cite
|
Sign up to set email alerts
|

Residents' waste mobile recycling planned behavior model: the role of environmental concern and risk perception

Abstract: PurposeThe purpose of this research is to investigate the relationships of environmental concern and risk perception with residents' waste mobile recycling behavior in the scenario of continuously increasing electronic waste (aka e-waste) around the world.Design/methodology/approachFor empirically testing proposed research model, this study utilized convenience sampling strategy and collected 346 responses from residents in the People’s Republic of China (PRC) through an online survey. The hypotheses were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…One definition of attitude is a person's overall assessment of a person's behavior (Chang et al, 2022). Attitude is the degree to which individual values or disvalues a given activity, as described by (Ajzen, 1991); Yuzhanin & Fisher, 2016).…”
Section: Literature Review Attitudesmentioning
confidence: 99%
“…One definition of attitude is a person's overall assessment of a person's behavior (Chang et al, 2022). Attitude is the degree to which individual values or disvalues a given activity, as described by (Ajzen, 1991); Yuzhanin & Fisher, 2016).…”
Section: Literature Review Attitudesmentioning
confidence: 99%
“…Liu et al (2020) revealed that subjective norms significantly impacted the purchase intention of green products in China. Similarly, the significant role of subjective norms on green purchase intention is also documented in different research contexts such as millennials in Pakistan (Qureshi et al, 2022), residents' waste mobile recycling behaviour in China (Chang et al, 2022), and green apparel in India (Joshi & Srivastava, 2020). However, the insignificant effect of the subjective norm on pro-environmental behaviour is also reported in the literature by (Hamzah and Tanwir, 2021;Nguyen and Nguyen, 2021;Xu et al, 2020).…”
Section: Subjective Normsmentioning
confidence: 75%
“…Numerous studies have been carried out on the factors that affect consumers' environmentally friendly behaviour such as green purchase intention or behaviour (Channa et al, 2022;Qureshi et al, 2022;Kautish & Sharma, 2021). These studies mainly utilized the Theory of Planned Behaviour (TPB) in exploring the factors influencing consumers in practising sustainable behaviour (Chang et al, 2022;Duong et al, 2022;Mazhar et al, 2022). Even though extant evidence has been found in the literature regardless of the factors of environmentally friendly behaviours, inconsistent findings were still reported (Emekci, 2019;Hamzah & Tanwir, 2021;Xu et al, 2020;Zheng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we hypothesize that the individuals' conscientiousness moderates the associations between individuals' COVID-19 fear and their intention towards eco-friendly behavior. Previous research has shown that several factors affect the individuals' attitude, subjective norm, and PBC, which subsequently lead to their behavior (Chang et al, 2022). In our study, it is expected that due to COVID-19 fear, people would like their important contacts to also demonstrate eco-friendly behavior.…”
Section: Introductionmentioning
confidence: 76%